2020
DOI: 10.1098/rsos.201261
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of male-biased sexual selection in a snake with conventional Darwinian sex roles

Abstract: Decades of research on sexual selection have demonstrated that ‘conventional’ Darwinian sex roles are common in species with anisogamous gametes, with those species often exhibiting male-biased sexual selection. Yet, mating system characteristics such as long-term sperm storage and polyandry have the capacity to disrupt this pattern. Here, these ideas were explored by quantifying sexual selection metrics for the western diamond-backed rattlesnake ( Crotalus atrox ). A significant standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…atrox , while the species exhibits characteristics that could promote male-biased sexual selection (e.g., male-male combat for access to females, male-biased sex ratio, and male-biased sexual size dimorphism), Levine et al [ 30 ] found no such pattern. In the population studied by Levine et al [ 30 ], high instances of multiple paternity were previously reported [ 33 ]. Furthermore, of 12 females for which multiple paternity litters were identified, 10 were radio-tracked over the mating season with both courtship and mating behaviors reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…atrox , while the species exhibits characteristics that could promote male-biased sexual selection (e.g., male-male combat for access to females, male-biased sex ratio, and male-biased sexual size dimorphism), Levine et al [ 30 ] found no such pattern. In the population studied by Levine et al [ 30 ], high instances of multiple paternity were previously reported [ 33 ]. Furthermore, of 12 females for which multiple paternity litters were identified, 10 were radio-tracked over the mating season with both courtship and mating behaviors reported.…”
Section: Discussionmentioning
confidence: 99%
“…In snakes, while there is limited evidence that sperm stored over multiple reproductive seasons can compete with spermatozoa from recent inseminations [ 1 , 12 , 24 , 32 , 55 ], general models show that overlapping ejaculates resulting in multiple paternity can erode the strength of post-copulatory sexual selection in males [ 1 , 25 , 54 ]. In studies investigating post-mating sexual selection, a primary aim is to measure the opportunity for sexual selection [ 25 , 54 ], or selection intensity acting directly on mate numbers using Bateman gradients or traits such as body size [ 28 30 , 33 , 54 , 56 , 57 ]. These types of evolutionary analyses would clearly profit from a broader understanding of LTSS in populations given the eroding effect it may have on sexual selection [ 24 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At capture, Global Positioning System (GPS) coordinates were obtained, and subjects were measured (snout-vent length, tail length, head dimensions to the nearest millimeter; body mass to the nearest 1.0 g) and sex confirmed (via probing) while under light anesthesia (isoflurane). Individuals were photographed, implanted with a unique passive integrated transponder (PIT) tag (AVID, Inc.), and their proximal rattle segments were colored via (Amarello et al, 2010;Greene et al, 2002;Levine et al, 2020Levine et al, , 2021Repp, 1998;Schuett, Clark, et al, 2016;. Shed cycle refers to skin shedding (ecdysis).…”
Section: Collecting and Processing Subjectsmentioning
confidence: 99%